2013
DOI: 10.1089/cyber.2012.0103
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Video Game Use on Time Perception: Differences Between Sub- and Multi-Second Intervals

Abstract: Even though video game players frequently report losing track of time while playing, few studies have addressed whether there are long-lasting effects of such activity on time perception. We compared the performance of chronic and occasional video game players in sub- and multi-second time perception tasks. Temporal Discrimination and Temporal Bisection tasks, in the range of 100 to 1,000 milliseconds, and Time estimation and Time production tasks, in the range of 5 to 60 seconds, were used to assess sub- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…69 • Puzzle game group improved in attention and visuo-spatial ability [81] matter volume of several brain areas predicted variability in learning of the game. Specifically, skill acquisition was linked to variance in gray matter volumes of the medial prefrontal cortex (Brodmann area 6), the cerebellum, the somatosensory area (PCG), the right ventral anterior cingulate cortex (ACC, Brodmann area 24), and the dorsolateral prefrontal cortex (DLPFC).…”
Section: Prospective Studies-structural and Functional Brain Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…69 • Puzzle game group improved in attention and visuo-spatial ability [81] matter volume of several brain areas predicted variability in learning of the game. Specifically, skill acquisition was linked to variance in gray matter volumes of the medial prefrontal cortex (Brodmann area 6), the cerebellum, the somatosensory area (PCG), the right ventral anterior cingulate cortex (ACC, Brodmann area 24), and the dorsolateral prefrontal cortex (DLPFC).…”
Section: Prospective Studies-structural and Functional Brain Effectsmentioning
confidence: 99%
“…Another examined variation in temporal discrimination and bisection task performance as well as time estimation and production task performance in nine chronic (>30 game playing hours per week) versus nine occasional (≤5 game playing hours per week) adolescent male (mean age approximately 16) video game players to assess time perceptions [81]. The authors report that due to chronic video game play, efficient time perception in players may be more inherent than cognitively controlled.…”
Section: Retrospective Studies-cognitionmentioning
confidence: 99%
“…Furthermore, the study almost reaching significant results [37] and the study yielding significant results [34] included pathological gamers, while the two studies without any significant results did not [33,35]. Thus, those scattered results could be explained by this difference in the population used.…”
Section: Discussionmentioning
confidence: 91%
“…Some studies showed a clear biased time perception (i.e., without clarifying the paradigm concerned, [34]) or a nearly significantly impaired one (i.e., in a retrospective paradigm, [33]), while other studies show no such association (i.e., in a prospective paradigm, [35,37]). This lack of significant results could be due to the short durations used (i.e., 60 seconds, [37]), or the way that time perception was assessed (i.e., not controlling the prospective and retrospective paradigm while measuring time perception, [35]; using a prospective paradigm, while retrospective time perception seems to be more important, [37]). However, the near significant results [33] may be explained by a lack of rigor because expertise in other games was not controlled for among novice gamers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation